A Case of Long-Term Survival with Own Liver in the Patient of Biliary Atresia Who Developed Hepatocellular Carcinoma - Tanaka, Yasunari; Masumoto, Kouji; Ishige, Kazunori; Fukuda, Kuniaki; Shinkai, Toko; Takayasu, Hajime (Archives of Clinical and Medical Case Reports, 2020)
Here we report a case of long-term survival with own liver in the patient of biliary atresia (BA) who developed hepatocellular carcinoma (HCC). The patient was a 34-year-old man. He underwent a portal jejunostomy with a diagnosis of BA (IIIb1ν) on the 94th day after birth, with a favorable post-operative course. Contrast-enhanced CT upon admission for cholangitis at the age of 34 suspected HCC, with an AFP level of 1.3 ng/ml and increased PIVKAII to 1,199 mAU/ml. He was diagnosed with HCC on MRI, and the tumor embolus had spread to the left branch of the portal vein; thus, resection and transplantation were considered contraindication. Proton therapy was performed, but he died 11 months after the detection of HCC. To date, 26 cases of HCC including this one have been reported, of which 20 were those in minors. Many of the patients with early onset have poor prognosis such as poor reduction of jaundice, while many of those with adult onset have relatively favorable prognosis as in this case; therefore, it was suggested that the progression of cholestatic cirrhosis is associated with carcinogenesis.